Fostering Social Participation in Inclusive Classrooms of Students who are Deaf. Issue 3 (4th May 2019) - Schwab, Susanne; Wimberger, Tanja; Mamas, Christoforos
ABSTRACT: Research indicates that children with hearing impairment are at higher risk regarding their social participation in school compared to their hearing peers. The purpose of this study was to investigate the social participation of 7th Grade students with hearing impairment in inclusive classrooms. Data from 62 7th Grade students across three classrooms and teachers were collected via paper-and-pencil questionnaires and from regular and special needs teachers via interviews. Results from the single case studies in three classrooms indicate that students with hearing impairment feel less socially integrated and less accepted by their peers. They do, however, interact more with other students with special needs and most students with hearing impairment have friends in their class. Teachers evaluated social integration, acceptance, interaction and friendships of their students with hearing impairment as average or as above average. The teachers' evaluations only partly correspond to the self-perceptions of the students. Factors that either promote or hinder participation on an institutional, teacher, teaching and student level were exposed, which may have important practice and policy implications.